2015
DOI: 10.4103/1793-5482.151515
|View full text |Cite
|
Sign up to set email alerts
|

Cavernomas: Outcomes after gamma-knife radiosurgery in Iran

Abstract: Background:Treatment of cavernomas remains a challenge in surgically inaccessible regions. The purpose of this study was to evaluate outcomes after gamma-knife surgery (GKS) for these patients.Materials and Methods:A retrospective review of 100 patients treated between 2003 and 2011 was conducted in order to evaluate hemorrhage rates, complications, radiation effects after GKS. Dosage at the tumor margin was stratified into two groups: those that received ≤13 Gy; and those who received >13 Gy. The demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The bleeding risk could be underestimated, but our intention was to avoid overestimation of the pretreatment hemorrhage rate in order to further validate SRS posttreatment results. Other authors have employed this equation before [16,21,22]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bleeding risk could be underestimated, but our intention was to avoid overestimation of the pretreatment hemorrhage rate in order to further validate SRS posttreatment results. Other authors have employed this equation before [16,21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…A significant volume reduction after GKRS was observed in 24 patients (61.5%). Azimi et al [21] reported a retrospective review of 100 patients. The radiation-related complication developed with a marginal dose of 13 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Pollock et al [40] 18 Gy, Kondziolka et al [65], and Liscak et al [66] applied a marginal dose of 16 Gy and tried to reduce ARE. Azimi et al [67], and Park and Hwang [68] prescribed a low marginal dose of 13 Gy on average (Table 2) [19,22,29,40,[66][67][68][69][70][71][72]. In 2019, Lunsford et al [32] wrote that the median radiation dose to the CM margin was 13 Gy to reduce hemorrhagic risk and radiation-induced complications.…”
Section: Dose Plan and Irradiation In Gamma Knife Radiosurgerymentioning
confidence: 99%